Damage to Polymer Coating on Facing Brick Surface in Operated Buildings. (2017) - Ginchitskaia, Iuliia; Yakovlev, Grigory; Kizinievich, Olga; Polyanskikh, Irina; Pervushin, Grigory; Taybakhtina, Polina; Balobanova, Iuliia
Abstract: The article describes the main reasons of efflorescence on the facing brick surface coated with polymer that leads to its delamination in operated buildings. To reduce efflorescence moisture, infiltration in the masonry should be reduced, the rate of which depends on the capillary porous structure of bricks. To control the porosity, building ceramic is suggested to be modified with multi-walled carbon nanotubes dispersions of Graphistrength CW 2-45, which enhances the structure of adobe, improves its sintering, increases the structure uniformity of ceramic fragments and efflorescence resistance. Ceramic matrix of the modified samples before and after firing has a dense and uniform microstructure with the minimum of deep interconnected pores. Adding carbon nanotubes in the amount of 0, 001% from the formed mass provides the modification of the ceramic matrix and improves its physical and mechanical properties by 30-35%.